2007
DOI: 10.1002/rcm.3311
|View full text |Cite
|
Sign up to set email alerts
|

Using calibration approaches to compensate for remaining matrix effects in quantitative liquid chromatography/electrospray ionization multistage mass spectrometric analysis of phytoestrogens in aqueous environmental samples

Abstract: Signal suppression is a common problem in quantitative liquid chromatography/electrospray ionization multistage mass spectrometric (LC/ESI-MS(n)) analysis in environment samples, especially in highly loaded wastewater samples with highly complex matrix. Optimization of sample preparation and improvement of chromatographic separation are prerequisite to improve reproducibility and selectivity. Matrix components are reduced if not eliminated by optimization of sample preparation steps. However, extensive sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 44 publications
3
45
0
3
Order By: Relevance
“…Some researchers have focused on optimising sample preparation to reduce matrix effect, while others have assessed the level of matrix effect and compensated for the alteration in signal by using an internal standard (IS), often a stable isotope-labelled analogue of the drug [29][30][31][32] or, if it is lacking, a structural analogue. However, in a multi-component analysis, finding an appropriate IS for every analyte might be difficult or impossible.…”
Section: Matrix Effectmentioning
confidence: 99%
“…Some researchers have focused on optimising sample preparation to reduce matrix effect, while others have assessed the level of matrix effect and compensated for the alteration in signal by using an internal standard (IS), often a stable isotope-labelled analogue of the drug [29][30][31][32] or, if it is lacking, a structural analogue. However, in a multi-component analysis, finding an appropriate IS for every analyte might be difficult or impossible.…”
Section: Matrix Effectmentioning
confidence: 99%
“…This undesirable matrix effects can be considered as one of the main LC-MS/MS drawbacks, mainly when an electrospray ionization source (ESI) is used [32]. To ensure an accurate quantification of analytes, different approaches are applicable in order to compensate for the matrix effects [33][34][35][36][37][38][39]. A simple method is the dilution of sample [35].…”
Section: Introductionmentioning
confidence: 99%
“…However, this is limited by the limits of detection required for the target compounds. The use of matrix-matched standards for calibration [36], is not much useful in environmental samples, as their composition vary in a broad range, and obtaining a blank of similar composition to sample is not easy. The standard additions method can provide accurate results [37], but in practice, it needs both a time-consuming sample preparation and evaluation of the obtained results and therefore is not much suitable for fast routine analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, matrix-matched calibration curves were used (Kang, Hick et al 2007;, and instrumental response was normalized to the appropriate SIS (E1-3S-d4 for all conjugates; E1-d4 for all free and halogenated forms).…”
Section: Correcting For Sample Processing Losses and Matrix Effectsmentioning
confidence: 99%
“…Since it was not practical to obtain or produce a wastewater matrix that was free of estrogens, we calculated matrix effects based on the ratio of the response factors (calibration curve slope) for estrogens spiked into wastewater matrix extracts and neat solvent (Kang, Hick et al 2007). The matrix effects observed in this study (see Table 1) are consistent with ion suppression reported in other studies of estrogens in wastewater matrices (Kang, Hick et al 2007;Backe and Field 2012).…”
Section: Matrix Effectsmentioning
confidence: 99%